Prediction of blood:air and fat:air partition coefficients of volatile organic compounds for the interpretation of data in breath gas analysis6Dedicated to the memory of our friend, colleague, and mentor Anton Amann. (27th January 2016) - Kramer, Christian; Mochalski, Paweł; Unterkofler, Karl; Agapiou, Agapios; Ruzsanyi, Veronika; Liedl, Klaus R
Abstract: In this article, a database of blood:air and fat:air partition coefficients ( λ b:a and λ f:a ) is reported for estimating 1678 volatile organic compounds recently reported to appear in the volatilome of the healthy human. For this purpose, a quantitative structure-property relationship (QSPR) approach was applied and a novel method for Henry's law constants prediction developed. A random forest model based on Molecular Operating Environment 2D (MOE2D) descriptors based on 2619 literature-reported Henry's constant values was built. The calculated Henry's law constants correlate very well ( R 2 test   =  0.967) with the available experimental data. Blood:air and fat:air partition coefficients were calculated according to the method proposed by Poulin and Krishnan using the estimated Henry's constant values. The obtained values correlate reasonably well with the experimentally determined ones for a test set of 90 VOCs ( R 2   =  0.95). The provided data aim to fill in the literature data gap and further assist the interpretation of results in studies of the human volatilome.